LncRNA NEAT1 promotes epithelial–mesenchymal transition in nasal polyp cells via the miR-199-3p/PAK4 axis - Shuman Li; Yu Jiang; Yalan Zhang; Bowen Zheng; Chao Yuan; Yang Shen; Yi Zhao; Tao Lu; Yucheng Yang (Frontiers in Immunology, 2025)
Background and purposeChronic rhinosinusitis with nasal polyps (CRSwNP) is a persistent inflammatory condition marked by high recurrence and limited therapeutic efficacy. This study investigates the role of long non-coding RNA NEAT1 in promoting epithelial–mesenchymal transition (EMT) in CRSwNP, focusing on its regulatory interaction with the miR-199-3p/PAK4 axis.MethodsNEAT1 expression was assessed in nasal epithelial cells from CRSwNP patients using qPCR and FISH. Primary human nasal epithelial cells and BEAS-2B cells were subjected to NEAT1 knockdown via siRNA. Cell migration, barrier function, and cytoskeletal dynamics were evaluated through scratch assays, Transwell migration, FITC-Dextran permeability testing, and phalloidin staining. EMT marker expression was analyzed via Western blotting and immunofluorescence. Transcriptome sequencing identified PAK4 as a downstream effector. In vivo validation was performed using a mouse nasal polyp model, and molecular interactions among NEAT1, miR-199-3p, and PAK4 were confirmed via dual-luciferase reporter assays. Rescue experiments further elucidated mechanistic pathways.ResultsIn comparison to controls, NEAT1 expression was significantly elevated in the epithelial tissues of CRSwNP. NEAT1 knockdown inhibited cell migration, enhanced epithelial barrier integrity, and reversed EMT-associated cytoskeletal remodeling. E-cadherin levels increased, while N-cadherin and vimentin decreased. Transcriptomic and functional analyses identified PAK4 as a NEAT1-regulated target. NEAT1 was shown to sponge miR-199-3p, thereby relieving its inhibitory effect on PAK4. Overexpression of miR-199-3p suppressed PAK4 and mitigated EMT-related changes induced by NEAT1.ConclusionNEAT1 promotes EMT in nasal polyp epithelial cells by modulating the miR-199-3p/PAK4 axis, highlighting its potential as a diagnostic biomarker and therapeutic target in CRSwNP.